1997
DOI: 10.1111/j.1432-1033.1997.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Analysis of gp17, a Natural CD4 Ligand from Human Seminal Plasma Inhibiting Human Immunodeficiency Virus Type‐1 gp120‐Mediated Syncytium Formation

Abstract: We have previously isolated from human seminal plasma a CD4 ligand, the gp17 glycoprotein, which shares sequence identity with three previously identified proteins : secretory actin-binding protein (SABP) from seminal plasma, gross-cystic-disease fluid protein-1 5 (GCDFP-15) and prolactin-inducible protein (PIP) from breast tumor cells. Functions of these glycoproteins are unknown. To further characterize the physical interaction between gpl7 and CD4 we used surface plasmon resonance and demonstrated that gp17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Earlier reports showed that PIP bind strongly with Fc fragment of IgG (Antisperm Antibody) and CD4 [22,43]. This finding indicates that presumably PIP also has strong affinity for ZAG.…”
Section: Discussionmentioning
confidence: 65%
“…Earlier reports showed that PIP bind strongly with Fc fragment of IgG (Antisperm Antibody) and CD4 [22,43]. This finding indicates that presumably PIP also has strong affinity for ZAG.…”
Section: Discussionmentioning
confidence: 65%
“…The seminal plasma gp17 binding site on CD4 is also located in the D1 domain, close to but distinct from the gp120-binding site (38).…”
Section: Il-16 Binding Domain On Cd4mentioning
confidence: 94%
“…The ability of PIP to bind a large array of proteins may account for its multifaceted role in various biological processes, such as fertility, immunoregulation, antimicrobial activity, apoptosis, and tumor progression [20]. In particular, the ability of PIP to bind to CD4 molecule and block CD4-mediated cell programmed death lead to the proposal that it may modulate adaptive immune responses [21][22][23][24][25]. The CD4 molecule plays a critical role in adaptive immunity by acting as a T-cell coreceptor for recognition of peptides bound to MHC class II molecules on APCs [26].…”
Section: Discussionmentioning
confidence: 99%